วิจารณ์หนังสือ : Book Review ธรรมะทวนกระแส - Chuntabong, Kanyarat (Journal of Graduate MCU KhonKaen Campus, 2022)
The review of this book mentioned that it transcends the terrifying. Because when humanity is fearful, or when we are frightened, our minds wander. Until we ignore the root cause of the problem, which is our own fear. To stay overnight for meditation in the forest in the heart of the valley where there is a lack of convenient things for living, should be open to touch and sense quiet nature used as a tool to soothe the mind to flourish in touch with Dhamma surrounding them. A heart that is in direct contact with nature will aid in the discovery of wisdom and truly happiness among difficulties. What goes on in the mind while you’re simply a passive observer is just a passive gaze, which might reveal a lot. What is going on in the mind is simply a passive view, which can only be accomplished by trusting comfortably and without being overwhelmed by cravings. Accept that the mind can manifest itself in a variety of ways. The rush and bustle of life in a big city. When you arrive at this location, you must be alone and focus solely on your body and thoughts.